The reasons behind the failure of Jahangir Khoja’s regime in Kashghar (Journal of Oriental Studies, 2021)
The failure of Jahangir’s revolt in Kashghar is one of the debatable topics in the colonial history of Eastern Turkestan. Kim and Millward reflect the military and political-economic perspectives on this event. Crossley attempted to explore the role of leadership, but her study lacks evidence from primary sources. The purposes of this article are the reinvestigation of Jahangir’s revolt from the foreign relations perspective and unification the previous theories under a common paradigm reevaluating the previous methodological structures. The paper will try to explain that the devastation of Jahangir’s regime was a result of the lack of trust between Qoqand and Kashghar rulers, a revised strategy of Chinese authorities and the influence of the local biis to Jahangir’s power. This essay is based on the synthesis of Russian and Persian ethnographical diary, political histories and secondary sources. Mainly, this study contributes to the religious history of Central Asian anticolonial movements. Key words: Khoja’s revolt, Qing dynasty, anticolonial movements, Islamic regime in Kashghar, Qoqand khanate.